TANGGUNG JAWAB PERUSAHAAN PUBLIK DALAM TRANSAKSI/YANG MENGADUNG BENTURAN KEPENTINGAN - Novanlie Holung (JURNAL AKTA YUDISIA, 2021)
The public company including the issuer that conducting conflict of interest transaction are generally harmful towards independent stock holder, because the transaction very susceptible if it linked to the personal economic interest of the Director, Commissioner and also the major shareholder. The public company including issuer are not prohibited from conducting all the transaction as long as they following the rules that have been implemented by the regulator which is state in OJK Regulation No. 42 of 2020 about conflict of interest transactions, the most important thing they should do is to obtain approval from the independent shareholders at the RUPS. Therefore, the problem which is surfaces is namely the position as well the legal protection of the independent shareholder.This research will be use Yuridis Normative research method, where the writer will be conducting a review towards library materials as well the secondary material to find a legal rules, legal principles and legal doctrines in order to answer the legal issues with a statutory and conceptual. The public companies openly state that they will conduct transaction that contain a conflict of interest, allowing independent shareholders to make decision through the RUPS LB. Generally, the process of conflict of interest transaction initially begins with the disclosure of information to the public or public investors and also the OJK, and then the progress continue with decision making around RUPS LB, the final decision of the independent share holder towards the transaction that contain a conflict of interest finally executed of conflict of interest based transactions around RUPS LB. Based on OJK regulation No. 21/POJK.04 / 2015 and OJK Circular No. 32/SEOJK.04/2015 requires public companies to implement corporate governance guidelines from publicly listed companies issued by the OJK to encourage the implementation of good governance practice in accordance with international practices that are exemplary.With this, it can hope can protect the independent shareholders in transactions that contain conflict of intrest that can be detrimental. The existence of approval is an important aspect in the principles of proportionality, with it proves that a transaction that contains a conflict of intrest is a fair transaction and is supported by the delivery of relevant information to all shareholders.